2016
DOI: 10.1055/s-0035-1569285
|View full text |Cite
|
Sign up to set email alerts
|

Stresserleben bei Medizinstudierenden: Welche Rolle spielen Bindungserleben und Persönlichkeitsaspekte?

Abstract: Significant correlations exist between attachment style and the level of structural integration of the personality, and burnout risk as well as stress burden. The level of structural integration of the personality mediates the relationship between the attachment-related "model of self" and stress experience, i. e. a positive "model of self" can have a stress-protective effect when good structural abilities are present. Practical implication: An insecure attachment style and a low level of structural integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
11
3
5
Order By: Relevance
“…However, we discovered that the medical students in the present sample had significantly lower depression and anxiety scores than a sample of first-semester medical students from a previous study by Bugaj et al (t(310) = 3.8035, p < 0.0002; t(309) = 2.897, p = 0.004) [57]. In addition, the post-score for mental health was significantly higher than the score for mental health of the sample of first-semester students in the study by Bugaj et al (t(310) = 3.424, p < 0.0001) [57]. We did not find any significant difference in the scores for physical health when comparing the two samples (t(310) = 0.723, p = 0.470).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, we discovered that the medical students in the present sample had significantly lower depression and anxiety scores than a sample of first-semester medical students from a previous study by Bugaj et al (t(310) = 3.8035, p < 0.0002; t(309) = 2.897, p = 0.004) [57]. In addition, the post-score for mental health was significantly higher than the score for mental health of the sample of first-semester students in the study by Bugaj et al (t(310) = 3.424, p < 0.0001) [57]. We did not find any significant difference in the scores for physical health when comparing the two samples (t(310) = 0.723, p = 0.470).…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, we did not find significant differences when comparing the post PHQ-9 scores and the post GAD-7 scores to representative norm samples (t(2086) = 1.1135, p = 0.266; t(5050) = 0.3437, p = 0.731) [65,66]. However, we discovered that the medical students in the present sample had significantly lower depression and anxiety scores than a sample of first-semester medical students from a previous study by Bugaj et al (t(310) = 3.8035, p < 0.0002; t(309) = 2.897, p = 0.004) [57]. In addition, the post-score for mental health was significantly higher than the score for mental health of the sample of first-semester students in the study by Bugaj et al (t(310) = 3.424, p < 0.0001) [57].…”
Section: Discussioncontrasting
confidence: 51%
“…The current study is the first to compare psychometric, psychophysiological, and humoral assessments of stress perception between international and local first-term medical students. In contrast to other studies [50,51], our study’s participants did not present significantly higher levels of stress with the exception of two measures: first, our sample’s students reported higher levels of depression in the PHQ-9 questionnaire at the beginning of the semester. However, as their scores only reached the cut-off values equivalent to ”minimal” depression symptoms, they should not be overrated [37].…”
Section: Discussioncontrasting
confidence: 99%
“…In a previous study conducted in 2016, Bugaj et al investigated psychological stress and possible protective factors in a sample of n = 293 first-year medical students. It was shown that students with a secure attachment style experienced significantly less stress than students with insecure attachment styles [31]. In addition, a positive “Model of the Self”, as part of the dimensional analysis of adult attachment, was also identified as stress-protective in medical students [31].…”
Section: Introductionmentioning
confidence: 99%